PREVALENSI INFESTASI KELOMPOK CACING STRONGIL PADA PEDET SAPI POTONG DI KABUPATEN KARANGANYAR - , MUHAMMAD HUZAIFAH ALI MUTAHARI, drh. Heru Susetya, MP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Group of strongyle infestation is disease caused by three superfamily Strongyloidea, Trichostrongyloidea, dan Ancylostomatoidea. with clinical signs can be anemic, diarrhea and enteritis. Group of strongyle infestation in calves may interfere with the growth and weight gain so that the condition is detrimental to breeders. This research was conducted to find out the prevalence of strongyle infestation in calves of Karanganyar District, and indentify risk factors for the incidence group of strongyle infestation. The sample is about 140 beef cattle calves feces of 121 breeders who was in Karanganyar. The sampling technique used in this research is dual stage, rambang simple, and clusters at the breeder level. Risk factors obtained by interviews based on the questionnaire. Data analysis was done by descriptive statistics and analysis of risk factors to do with the association test (Ï2 The result showed the prevalence group of strongyle infestation in calves of Karanganyar District is about 27,85% (39/140). The risk factors which associated with group of strongyle infestation infection in Karanganyar are colostrums intake, types of cages individual or group and the presence or absence receptacle feces disposal.